A comparison of methods for calculating notch tip strains and stresses under multiaxial loading (Fracture and Structural Integrity, 2016)
Selected methods for calculating notch tip strains and stresses in elastic–plastic isotropic bodies subjected to multiaxial monotonic loading were compared. The methods use sets of equations where hypothetical notch tip elastic strains and stresses obtained from FEM calculations serve as an input. The comparison was performed within two separate groups of methods: the first group consists of the methods intended for cases of multiaxial proportional loading and the second group deals with multiaxial non-proportional loading. Originally, the precision of the methods was validated by comparison with results obtained from elastic–plastic FEM analyses. Since computer performance at the time was lower than nowadays, verification of the proposed methods on FEM models with a finer mesh was needed. Such verification was carried out and is presented in this paper. The effect of various formulations of material stress–strain curve was also evaluated.
Keywords: Notch stresses; Multiaxial loading; FEM; Neuber’s rule; ESED rule